2014
DOI: 10.1007/s00436-014-4119-y
|View full text |Cite
|
Sign up to set email alerts
|

Antiplasmodial activity-aided isolation and identification of quercetin-4’-methyl ether in Chromolaena odorata leaf fraction with high activity against chloroquine-resistant Plasmodium falciparum

Abstract: The present study was undertaken to evaluate the antiplasmodial activity of Chromolaena odorata leaf extract and gradient fractions through in vivo and in vitro tests, aimed at identifying its antiplasmodial constituents. Sub-fractions obtained from the most active gradient fraction were further tested for cytotoxicity against THP-1 cells, chloroquine-sensitive (HB3) and chloroquine-resistant (FCM29) Plasmodium falciparum. Our results showed the dichloromethane gradient fraction was most effective, significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 25 publications
0
28
0
1
Order By: Relevance
“…41 Saponins, flavonoids and tannins have been suggested to act as primary antioxidant or free radicals scavengers that can counteract the oxidative damage induced by the malaria parasite. 42 The antimalarial activities of the n-butanol fraction observed in this study may therefore have been due to the presence of these phytochemicals exerting their activity through one or both of these mechanisms, or may be even through a yet to be identified mechanism. The chemosuppression produced by the n-butanol fraction of Uapaca togoensis in the current study was in agreement with other studies which reported that the nbutanol fraction of medicinal plants like Asparagus africanus 43 and Dodonaea angustifolia 38 possesses significant antimalarial activity compared to the other fractions studied.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…41 Saponins, flavonoids and tannins have been suggested to act as primary antioxidant or free radicals scavengers that can counteract the oxidative damage induced by the malaria parasite. 42 The antimalarial activities of the n-butanol fraction observed in this study may therefore have been due to the presence of these phytochemicals exerting their activity through one or both of these mechanisms, or may be even through a yet to be identified mechanism. The chemosuppression produced by the n-butanol fraction of Uapaca togoensis in the current study was in agreement with other studies which reported that the nbutanol fraction of medicinal plants like Asparagus africanus 43 and Dodonaea angustifolia 38 possesses significant antimalarial activity compared to the other fractions studied.…”
Section: Resultsmentioning
confidence: 90%
“…21 This difference in antimalarial activity may be linked to the fact that the ethyl acetate fraction was devoid of saponins and tannins and studies have reported these phytochemicals to possess antimalarial activity. 42 Research on medicinal plants contributed to the isolation of compounds with potent antimalarial activity including artemisinin and quinine. Thus the isolation of compounds from the n-butanol fraction of U. togoensis is desirable as this may lead to the discovery of lead compounds which could be further adjusted by semi-synthetic approaches to obtain effective antimalarial agents.…”
Section: Resultsmentioning
confidence: 99%
“…Terpenoids, flavonoids, saponin, alkaloids, quercetin and kaempferol were known to have antimalarial activity and antioxidant activity which might also play antimalarial activity [24,25]. It has been reported and suggested that quercetin and kaempferol presented antimalarial activity against in vitro culture of Plasmodium falciparum and P. berghei infected mice [26,27]. In addition, antimalarial activity of these compounds was found evidently on the ring stage of the malaria parasite [28].…”
Section: Discussionmentioning
confidence: 99%
“…[23] Its active phytochemical substances are as follows: (1) flavonoid aglycones (flavanones, flavonols, flavones) including acacetin, chalcones, eupatilin, luteolin, naringenin, kaempferol, quercetin, quercetagetin, and sinensetin;[2425262728293031] (2) terpenes and terpenoids;[32] (3) essential oils;[333435363738] (4) alkaloids including pyrrolizidine;[394041] (5) saponins and tannins;[23] (6) phenolic acids including ferulic acid, protocatechuic acid;[42] (7) phytoprostane compound including chromomoric acid. [43]…”
Section: Phytochemical Substancesmentioning
confidence: 99%
“…From review literature regarding the traditional uses, phytochemical properties of C. odorata are anti-bacterial,[27444344454647] anticancer,[2148] anticonvulsant,[49] antidiabetic,[505152] anti-diarrheal,[5354] anti-fungal,[5556] anti-inflammatory,[575859] antioxidant,[606162636465] and antiparasitic,[3040] hemostatic and wound healing,[1522236669] and hepatoprotective activities. [7071]…”
Section: Traditional Usesmentioning
confidence: 99%